Complex Chronic Wound Biofilms Are Inhibited in vitro by the Natural Extract of Capparis spinose - Di Lodovico, Silvia; Bacchetti, Tiziana; D’Ercole, Simonetta; Covone, Sara; Petrini, Morena; Di Giulio, Mara; Di Fermo, Paola; Diban, Firas; Ferretti, Gianna; Cellini, Luigina (Frontiers in Microbiology, 2022)
Resistant wound microorganisms are becoming an extremely serious challenge in the process of treating infected chronic wounds, leading to impaired healing. Thus, additional approaches should be taken into consideration to improve the healing process. The use of natural extracts can represent a valid alternative to treat/control the microbial infections in wounds. This study investigates the antimicrobial/anti-virulence effects of Capparis spinose aqueous extract against the main chronic wound pathogens: Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans. The extract shows phenolic characterization with the rutin (1.8 ± 0.14g/mg) as the major compound and antibacterial effect against bacteria (S. aureus PECHA 10 MIC 6.25%; P. aeruginosa PECHA 4 MIC 12.50%) without action against C. albicans (MIC and MFC ≥ 50%). Capparis spinose also shows a significant anti-virulence effect in terms of anti-motility/anti-biofilm actions. In particular, the extract acts: i) on P. aeruginosa both increasing its swimming and swarming motility favouring the planktonic phenotype and reducing its adhesive capability; ii) on S. aureus and P. aeruginosa biofilm formation reducing both the biomass and CFU/ml. Furthermore, the extract significantly displays the reduction of a dual species S. aureus and P. aeruginosa Lubbock Chronic Wound Biofilm, a complex model that mimics the realistic in vivo microbial spatial distribution in wounds. The results suggest that C. spinose aqueous extract could represent an innovative eco-friendly strategy to prevent/control the wound microbial infection.